ChemInform Abstract: Synthesis of 2‐Acylphenol and Flavene Derivatives from the Ruthenium‐Catalyzed Oxidative C—H Acylation of Phenols with Aldehydes. Issue 31 (August 2015) - Lee, Hanbin; Yi, Chae S.
Abstract The cationic ruthenium hydride complex catalyzes the oxidative C‐H coupling of phenols with aldehydes to furnish 2‐acylphenols, whereas the reaction of phenols with α, β‐unsaturated aldehydes affords flavene derivatives selectively.